Database " I&D”" First Experience with Microisis Software, Version 3.0 Multi-Trial Version- - Chacón Alvarado, Lucía (1994)
Standardization facilitates communication and enables the exchange of information with any national or international. This goal is possible through communication formats for automated information exchange as ECLAC, MARC., FCC. The School of Library, Documentation and Information of the National University MICROISIS software used for teaching network. The databases are designed using the MARC format and AACR2 bibliographic description. We report our experience with the database "R & D" on rural development, presenting the Field Definition Table, worksheet, the display format and selection table fields.